Voodoo and Power : The Politics of Religion in New Orleans, 1881-1940 - Roberts, Kodi A., 1979- (Book collections on Project MUSE., 2015)
"The racialized and exoticized cult of Voodoo occupies a central place in the popular image of the Crescent City. But as Kodi A. Roberts argues in Voodoo and Power, the religion was not a monolithic tradition handed down from African ancestors to their American-born descendants. Instead, a much more complicated patchwork of influences created New Orleans Voodoo, allowing it to move across boundaries of race, class, and gender. By employing late nineteenth and early twentieth-century first-hand accounts of Voodoo practitioners and their rituals, Roberts provides a nuanced understanding of who practiced Voodoo and why."--Publisher's description.